AB0076 Analysis for The Gene Expression Profiles in Rheumatoid Synovial Fibroblasts Regulated by Light. (15th July 2016) - Maeda, T.; Miura, Y.; Fukuda, K.; Hayashi, S.; Kurosaka, M.
Abstract : Background: Rheumatoid Arthritis (RA) is an autoimmune disease characterized by over-proliferation of synovial tissues and subsequent joint destruction [1]. Lymphotoxin-like, exhibits inducible expression, and competes with herpes simplex virus glycoprotein D for herpes virus entry mediator, a receptor expressed on T lymphocytes (LIGHT) is a member of tumor necrosis factor (TNF) receptor superfamily and is expressed on antigen-presenting cells through the activation of T cells. LIGHT modulates T-cell activation and promotes inflammation through the activation of nuclear factor (NF)κB by binding to its specific receptors herpes virus entry mediator (HVEM) and lymphotoxin (LT)-βR [2]. Furthermore, decoy receptor 3 (DcR3) competitively binds soluble LIGHT and inhibits LIGHT signaling via HVEM [3, 4]. Studies have suggested that LIGHT is overexpressed in RA fibroblast-like synoviocytes (RA-FLS) and production of TNFα is induced by stimulation with LIGHT, and that LIGHT may be related to autoimmune diseases such as inflammatory bowel disease or multiple sclerosis [5]. Objectives: In this study, we investigated the genes regulated by LIGHT in RA-FLS by comprehensive genetic analysis using microarrays to elucidate the involvement of LIGHT in RA pathogenesis. Methods: Microarray assay. Four individual lines of primary cultured RA-FLS were incubated with either 1.0 μg/ml recombinant human LIGHT protein or phosphate buffered saline (PBS) diluted with serum-free Opti-MEM medium as non-stimulated control for 12 hours at 37°C with 5% CO2. Gene expression was detected using cDNA microarray assay (Human Genome U133 Plus 2.0, GeneChip® 3' Expression Array, Affymetrix), and the gene expression profiles of LIGHT-stimulated cells and controls were compared. Real-time polymerase chain reaction (real-time PCR). The four most highly up- and down-regulated genes were discovered by comprehensive genetic analysis using the microarray. The relative mRNA expression levels of those genes were compared using TaqMan® real-time PCR on a StepOne™ real-time PCR system. Results: Microarray assay. The microarray analysis revealed that 1042 genes were up-regulated and 801 genes were down-regulated more than twofold by stimulation with LIGHT in RA-FLS. Expression of LIGHT-related genes in RA-FLS. The real-time PCR analysis confirmed that mRNA expression of the top-four genes up-regulated and those down-regulated was actually regulated by LIGHT. Conclusions: To our knowledge, this is the first report on the expression profiles of genes regulated by LIGHT in RA-FLS, which suggested the involvement of LIGHT-HVEM/DcR3 signaling in the pathogenesis of RA. References: Alamanos Y, et al. Autoimmun Rev. 2005 Mar;4:130–6. Murphy TL, Murphy KM. Annu Rev Immunol. 2010;28:389–411. Ware CF. Immunol Rev. 2008 Jun;223:186–201. Wang Y, et al. Immunol Rev. 2009 May;229(1):232–43. Steinberg MW, et al. Immunol Rev. 2011 Nov;244(1):169–87. Disclosure of Interest: None declared